Analisis dan Pengukuran Tingkat Eksposur Resiko Teknologi Informasi dengan Metode Fmea Pada PT. Bank Central Asia, Tbk - Kurniawan, Roy (Bina Nusantara University, 2014)
The purpose of this paper is to help the PT. Bank Central Asia, Tbk in measuring the level of risk exposure and identify the need to control IT risk management at PT. Bank Central Asia, Tbk. Conducted research methodology, field observation, library research, interviews and gave questionnaires to the relevant parties, perform data analysis, as well as measuring the risk of using the approach of FMEA (Failure Mode and Effect Analysis). The results achieved in this study is to facilitate the management in making decisions related to the design, maintenance, and development of information technology at PT. Bank Central Asia, Tbk and also minimize the risk of the failure so that the utilization of existing information technology can provide more optimal results. The conclusion from this study is that there is a risk of potential failure that could hamper the existing business processes in PT. Bank Central Asia, Tbk. Highest risk or potential failure according to theRPN (Risk Priority Number) is a software and hardware damage, as well as the corrupted database due to the impact of operational risk.